IMPLEMENTASI PROGRAM PEMBIASAAN KEGIATAN KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS ANAK DI RA AL-FATIH KURIPAN SUGIHAN - Sa'diyah, Khalimatus; Muh. Wasith Achadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The formation of religious character in early childhood is the main foundation for building a generation of faith and piety. This study aims to describe: (1) the form of religious activity habituation programs, (2) program implementation mechanisms, and (3) the results of program implementation on the formation of children's religious character at RA Al Fatih Kuripan Sugihan, Cilacap Regency. This research used a descriptive qualitative approach with field research. Data were collected through observation, in-depth interviews, and documentation with teachers and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that the religious habituation program includes: daily manners assessment (including: reciting prayers before and after learning, before and after eating, saying greetings, shaking hands with teachers and peers), practical worship (including: wudhu practice, prayer practice, memorizing short surahs, and reading Iqra), and introduction to Arabic letters and exemplary stories (about prophets, figures, and kyai). The program is implemented routinely and consistently every day through habituation, exemplary, advice, and reward methods. The implementation is proven to be able to shape children's religious character as reflected in behavioral changes, increased discipline, and the formation of religious habits in daily life.